PPE38-Secretion-Dependent Proteins of M. tuberculosis Alter NF-kB Signalling and Inflammatory Responses in Macrophages - Gallant, James; Heunis, Tiaan; Beltran, Caroline; Schildermans, Karin; Bruijns, Sven; Mertens, Inge; Bitter, Wilbert; Sampson, Samantha L. (Frontiers in Immunology, 2021)
It was previously shown that secretion of PE-PGRS and PPE-MPTR proteins is abolished in clinical M. tuberculosis isolates with a deletion in the ppe38-71 operon, which is associated with increased virulence. Here we investigate the proteins dependent on PPE38 for their secretion and their role in the innate immune response using temporal proteomics and protein turnover analysis in a macrophage infection model. A decreased pro-inflammatory response was observed in macrophages infected with PPE38-deficient M. tuberculosis CDC1551 as compared to wild type bacteria. We could show that dampening of the pro-inflammatory response is associated with activation of a RelB/p50 pathway, while the canonical inflammatory pathway is active during infection with wild type M. tuberculosis CDC1551. These results indicate a molecular mechanism by which M. tuberculosis PE/PPE proteins controlled by PPE38 have an effect on modulating macrophage responses through NF-kB signalling.